Characteristics of patients who use yoga for pain management in Indian yoga and naturopathy settings: a retrospective review of electronic medical records - Nair, Pradeep M. K.; Kriplani, Sucheta; Kodali, Prakash Babu; Maheshwari, Ayush; Bhalavat, Kinjal Dilipsinh; Singh, Deepika; Saini, Sanjeev; Yadav, Dinesh; Keswani, Jyoti; Silwal, Karishma; Sharma, Hemanshu; Tewani, Gulab Rai (Frontiers in Pain Research, 2023)
Objectives The aim of this study is to identify the characteristics of patients who underwent yoga therapy for pain in yoga and naturopathy clinical settings in India. Methods Electronic medical records of patients who received yoga therapy for pain in three inpatient yoga and naturopathy hospitals were reviewed retrospectively from January 2021 to September 2022. Demographic characteristics and details on pain condition, socioeconomic status, comorbidities, ancillary therapies received, and insurance status were collected. In addition, we prospectively collected data on adherence to yoga practice through a telephonic interview. Results A total of 984 patients were identified from a pool of 3,164 patients who received yoga therapy for pain for an average of 9.48 (1.13) days. Patients aged between 8 and 80 underwent therapy for varying pain conditions and diseases that include pain in the extremities, pain due to infection, trauma, degenerative diseases, autoimmune diseases, and spine and neurological diseases. The majority of the patients were females (66.3%), from middle class families (74.8%), and who did not have any insurance coverage (93.8%). Most of the patients were under naturopathy treatment (99.8%), followed by ayurveda (56%), and physiotherapy (49.3%), along with yoga therapy. All patients reported a significant reduction in pain post-integrated yoga therapy (p < 0.001). Adherence to yoga was significantly associated with underlying pain conditions, the presence of comorbidities, the types of therapies used, and socioeconomic status (p < 0.001). Conclusion This study highlights the real-time application of yoga in pain management in Indian yoga and naturopathy settings, as well as implications for future research.